Comparison of the Effectiveness of Acceptance and Commitment–Based Couple Therapy and Integrative Couple Therapy on Dysfunctional Beliefs, (Cognitive/Experiential) Avoidance, Conflict Resolution, and Sexual Satisfaction in Infertile Couples - Haji Abbasi, Samaneh; Saffarinia, Majid; Rezaie, Ali Mohammad (Applied Family Therapy Journal (AFTJ), 2026)
Objective: This study aimed to compare the effectiveness of Acceptance and Commitment–Based Couple Therapy (ACT-C) and Integrative Couple Therapy (IBCT) on dysfunctional relationship beliefs, cognitive and experiential avoidance, conflict resolution styles, and sexual satisfaction in infertile couples. Methods and Materials: Using a quasi-experimental pretest–posttest–follow-up design with a control group, infertile couples were recruited through purposive sampling and randomly assigned to ACT-C, IBCT, or a waitlist control. Both interventions were delivered in twelve 90-minute sessions across three months. Standardized self-report measures assessed dysfunctional relationship beliefs, cognitive and experiential avoidance, conflict resolution styles, and sexual satisfaction at pretest, posttest, and three-month follow-up. Data were analyzed using repeated-measures analysis of variance, followed by Bonferroni post hoc comparisons to examine within- and between-group differences over time. Findings: Repeated-measures analyses revealed significant group × time interaction effects for dysfunctional beliefs (total score and selected components), experiential avoidance, and conflict resolution dimensions, indicating differential change trajectories across groups (p < .05). ACT-C produced significantly greater reductions than IBCT in belief in the destructiveness of disagreement, belief in spouse unchangeability, total dysfunctional beliefs, and experiential avoidance (p < .05). ACT-C also led to greater improvements in positive problem solving and greater reductions in withdrawal and compliance compared with IBCT (p < .05). No significant between-group differences were found for cognitive avoidance. Both ACT-C and IBCT demonstrated significant improvements over time relative to the control group on sexual satisfaction components and total score; however, between-therapy differences on sexual satisfaction were not statistically significant (p > .05). Treatment gains were largely maintained at follow-up. Conclusion: Both ACT-C and IBCT are effective interventions for improving relational and sexual outcomes in infertile couples, with ACT-C showing incremental advantages on experiential avoidance, specific dysfunctional beliefs, and key conflict resolution styles, suggesting added value of flexibility-focused processes in this population.